The Impact of Rewards in the eExploitation of the Innovation Potential of the Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): Are the various types of rewards important for the use of the innovation potential in an organization? How do monetary rewards affect the use of innovation potential? Does the gender, age and education of employees influence the remuneration method? Is the cash prize for employees the greatest incentive for innovation?Purpose: The purpose is to record the existing state of innovation in the organization concerned and then take action to implement them. The main purpose is for employees to understand the essence of innovation and change the mindset of discovering and delivering them. Innovation benefits both individuals and the whole organization.Method: The quantitative method, the survey questionnaire covers 12 questions and the processing of results with frequency distribution.Results: The results of the survey showed that the way of rewarding depends on gender, age and level of education, and the cash prize is the best motivation for innovation and creativity.Organization: The acquisition of this type of information was of key importance for the organization, since it has not been known to date by the innovations or benefits of the proposals. After the survey, the company organized and adopted a new rule on innovations - useful suggestions, and systematically began to interpret the mindset in discovering and innovating. The first and basic question of employees was "What is innovation at all?". The greatest part of the task was to explain or change the mindset of giving innovations.Society: More favourable results for using our products are shown. Due to more reliable production, the organizations are more competitive, productivity increases, the cost of non-quality decreases, and emissions into the environment are reduced.Originality: In the organization concerned, the implementation of such a survey was carried out for the first time. We got information about how employees look at innovation, what it means to them, and how they understand innovation. It is also important that we get the information which of the proposed awards is most imply to them.Limitations/Future Research: The research was conducted only in one organization and it would have to be done in a few other ways to get a wider picture of what is happening in companies about motivating and rewarding employees, and it would be advisable to compare companies before and after the introduction of the use of innovation potential.
Keywords: innovation; motivation; rewarding